Failure behavior of copper Laser-Welded joints in lap shear specimens. (15th June 2022) - Devi, N.; Lin, P.-C.; Liu, Y.-J.; Tsai, T.-Y.; Chen, K.-T.; Hong, S.-T.; Tran, X.V.
Highlights: Failure analyses for LWed LS specimens made of Cu sheets were conducted. Failure modes & fracture mechanisms of Cu LWs were studied by micrographs. A damage criterion of Cu comprised of ε ¯ D pl and η was developed. 2D FE models of LWs were developed to simulate failure behavior and mode. Predicted failure behaviors of LWs show well agreement with experimental results. Abstract: In this study, the failure behavior of laser-welded (LWed) lap shear (LS) specimens in copper (Cu) sheets with unequal thickness has been studied through experimental and numerical approaches. LWed LS specimens with unequal thickness represented the tab-to-electrode joints of batteries in a module. Quasi-static tensile testing has been performed for studying the load–displacement curves, failure loads, and failure modes of LS specimens and the stress–strain curve of Cu. Microstructures and failure modes of LWs have been examined by exploring the micrographs before and after the failure. Necking failure was observed at the heat affected zone (HAZ) in the upper right sheet of LWed LS specimens. Microhardness distributions of LWs were obtained to estimate the stress–strain curves of the fusion zone (FZ), HAZ, and base metal (BM). Based on the stress–strain curves, a two-dimensional plane strain finite element model has been developed for LWed LS specimens. In order to develop a damage criterion for finite element models to simulate the failure mode of LWed LS specimens, a series of quasi-static tensile tests for one shear, one smooth, and four notched specimens made of Cu were conducted to derive the equivalent plastic strains at the onset of damage ε ¯ D pl and the corresponding triaxialities η . A damage criterion of BM (Cu) comprised of ε ¯ D pl and η was developed. Then a damage criterion of HAZ where the necking failure occurred was estimated based on the damage criterion of BM and the maximum values of ε ¯ D pl and η in HAZ derived by the finite element model subjected to the failure load. Finally, it has been concluded that based on stress–strain curves of FZ, HAZ, BM, damage criterion of HAZ, computational simulations of failure behavior of LWed LS specimens are in good agreement with the experimental results..